Building Green - Rademacher, Anne (University of California Press, 2017)
Building Green explores the experience of environmental architects in Mumbai, one of the world's most populous and population-dense urban areas and a city iconic for its massive informal settlements, extreme wealth asymmetries, and ecological stresses. Under these conditions, what does it mean to learn, and try to practice, so-called green design? By tracing the training and professional experiences of environmental architects in India's first graduate degree program in Environmental Architecture, Rademacher shows how environmental architects forged sustainability concepts and practices and sought to make them meaningful through engaged architectural practice. The book's focus on practitioners offers insights into the many roles that converge to produce this emergent, critically important form of urban expertise. At once activists, scientists, and designers, the environmental architects profiled in Building Green act as key agents of urban change whose efforts in practice are shaped by a complex urban development economy, layered political power relations, and a calculus of when, and how, their expert skills might be operationalized in service of a global urban future.